Pengaruh Good Corporate Governance, Corporate Social Responsibility dan Earnings Management terhadap Kinerja Keuangan Perusahaan - Retnaning Tyas Utami; Dewita Puspawati (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study aims to determine the effect of Good Corporate Governance (GCG), Corporate Social Responsibility (CSR), and Earnings Management on the Financial Performance of Mining Sector Companies listed on the Indonesia Stock Exchange (IDX) in 2022-2024. Twenty-eight companies were sampled. The research method used was quantitative research. Data were analyzed through multiple linear regression using SPSS 27. The results showed that GCG mechanisms, including institutional ownership, audit quality, and an independent board of commissioners, corporate social responsibility, and earnings management significantly impact financial performance.